CLINOHUMITE ASSOCIATED WITH K-RICHTERITE IN THE KOLLEKTIVNAYA KIMBERLITE PIPE - Taskayev V.I.; Ilupin I.P. (My University, 1990)
While examining rock fragments from the Kollektivnaya kimberlite pipe, the authors noticed a small kimberlite lump and, on its edge, observed an intergrowth of two minerals, brownish-red and green. Subsequent microprobe analysis allowed us to identify them, respectively, as clinobumite and an alkalic potassium-sodium amphibole, richterite. Both minerals are rare and have never before been found intergrown in kimberlite. Nor has clinohumite in Yakutian kimberlite bodies ever before been found intergrown with a mineral whose upper stability limit extends into the magmatic pressure-temperature range.